The Paradox of Implementing Restorative Justice at the Investigation Stage: A Systematic Weakening of Sentence Enhancement for Repeat Offenders - Adiningsih, Yufiyandini; Batubara, Gialdah Tapiansari (SIGn Jurnal Hukum, 2025)
The progressive adoption of restorative justice at the investigation stage has created the unintended consequence of systematically weakening law enforcement against repeat offenders. This study aims to analyze how the normative framework of restorative justice, particularly Police Regulation Number 8 of 2021, and its field implementation create a juridical gap that directly neutralizes the sentence enhancement mechanism. Employing juridical-normative and juridical-empirical approaches, this study confronts the ideal legal text (das sollen) with the practical reality (das sein) at the Criminal Investigation Unit of the Sumedang Regency Police. Key findings indicate that the regulation’s definition of recidivism, which is exclusively tied to a “court judgment,” renders restorative settlement records—which are purely administrative in nature—devoid of juridical evidentiary force. Consequently, offenders who repeatedly utilize the restorative path will always be considered first-time offenders. This condition opens a dangerous loophole for impunity and the weakening of the deterrent effect. This study concludes that without a policy reconstruction that grants limited legal status to restorative records and integrates them into a unified criminal justice data system, the noble goal of restorative justice risks sacrificing the principles of legal certainty and public protection. Therefore, urgent regulatory reform is necessary to synchronize the objective of restoration with the imperative of effective law enforcement against repeat offenders.